In situ structural evolution of single particle model catalysts under ambient pressure reaction conditions1. Issue 1 (11th December 2018) - Fernández, Sara; Gao, Lu; Hofmann, Jan Philipp; Carnis, Jérôme; Labat, Stéphane; Chahine, Gilbert A.; van Hoof, Arno J. F.; Verhoeven, M. W. G. M. (Tiny); Schülli, Tobias U.; Hensen, Emiel J. M.; Thomas, Olivier; Richard, Marie-Ingrid
Abstract : In situ evolution of the strain and lattice orientation of single particle model catalysts. Abstract : The catalytic activity of metal nanoparticles can be altered by applying strain, which changes the crystalline lattice spacing and modifies the electronic properties of the metal. Understanding the role of elastic strain during catalytic reactions is thus crucial for catalyst design. Here, we show how single highly faceted Pt nanoparticles expand or contract upon interaction with different gas atmospheres using in situ nano-focused coherent X-ray diffraction imaging. We also demonstrate inter-particle heterogeneities, as they differ in development of strain under CO oxidation reaction conditions. The reported observations offer new insights into the design of catalysts exploiting strain effects.